2015
DOI: 10.1590/0104-1428.1779
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da modificação química na solubilidade e intumescimento de microesferas à base de goma do cajueiro carboximetilada e quitosana

Abstract: ResumoEsferas de goma do cajueiro carboximetilada e quitosana foram produzidas via complexação polieletrolítica. As esferas foram modificadas quimicamente de modo a obter-se sistemas estáveis em meio ácido e que apresentassem uma resposta de intumescimento diferenciado frente à variação de pH. As esferas foram modificadas por reacetilação da quitosana e por reticulação com epicloridrina, glutaraldeído e genipina. As esferas reticuladas foram caracterizadas por meio de técnicas como: espectroscopia de absorção … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Chitosan has the characteristic of solubility in acidic media because of the free amino groups being protonated (NH3 +), where the precipitation tendency increases from the moment the pH approaches 6.0, regarding the increase of -NH2 clusters in the molecular structure. Thus, amino groups make it possible for them to bind to negatively charged materials, such as other polysaccharides, enzymes, and cells, being insoluble in water, concentrated acids, acetone, and alcohol [76][77][78].…”
Section: Chitin To Chitosan Conversionmentioning
confidence: 99%
“…Chitosan has the characteristic of solubility in acidic media because of the free amino groups being protonated (NH3 +), where the precipitation tendency increases from the moment the pH approaches 6.0, regarding the increase of -NH2 clusters in the molecular structure. Thus, amino groups make it possible for them to bind to negatively charged materials, such as other polysaccharides, enzymes, and cells, being insoluble in water, concentrated acids, acetone, and alcohol [76][77][78].…”
Section: Chitin To Chitosan Conversionmentioning
confidence: 99%
“…The control sample also shows the same absorption profile with the characteristic bands, but with little intensity. Monteiro et al (2015) also found similarity between the FTIR spectra of their polyelectrolyte complexes in the formation of microspheres and the spectra of their wall materials. 2018prepared an apple pomace polyphenolic extract loaded into biodegradable and commercially available natural polymer such as maltodextrin and identified the functional groups of the active components and also any interaction modes between the polymeric wall and the polyphenolic core by FTIR.…”
Section: Ft-ir Spectroscopymentioning
confidence: 57%
“…Thus, amino groups enable them to attach with negatively charged particles, which include other polysaccharides, enzymes, as well as cells, while remaining impermeable in water, highly concentrated acids, acetone, and ethanol. [169][170][171] Several studies on chitosan have been conducted in the past few years, demonstrating a solid link among both the structural as well as morphological aspects of chitin, chitosan, and related compounds, as well as their qualities and possible uses. 172 This kind of polymer is commonly present in tiny amounts in the cell walls of certain fungi (Zygomycetes), or it may be produced by acidic hydrolysis of chitin from crustaceans as well as arthropod exoskeletons.…”
Section: Chitin To Chitosan Conversionmentioning
confidence: 99%
“…Chitosan is readily soluble in acidic solutions due to the protonation of free amino groups (NH 3 + ), and its precipitating tendency rises when the pH exceeds 6.0, indicating a rise in NH 2 complexes in the structure of the molecules. Thus, amino groups enable them to attach with negatively charged particles, which include other polysaccharides, enzymes, as well as cells, while remaining impermeable in water, highly concentrated acids, acetone, and ethanol 169–171 . Several studies on chitosan have been conducted in the past few years, demonstrating a solid link among both the structural as well as morphological aspects of chitin, chitosan, and related compounds, as well as their qualities and possible uses 172 .…”
Section: Chitin To Chitosan Conversionmentioning
confidence: 99%